2019
DOI: 10.2147/ceg.s216188
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative esophagogastroduodenoscopy in patients without reflux symptoms undergoing laparoscopic sleeve gastrectomy: utility or futility?</p>

Abstract: Aim To evaluate the value of esophagogastroduodenoscopy (EGD) as a preoperative investigation in individuals without symptoms of Gastro-Esophageal Reflux Disease (GERD) who will undergo laparoscopic sleeve gastrectomy (LSG). Materials and methods After Institutional Review Board approval was obtained, patients scheduled for LSG were prospectively enrolled in the study between January 2016 and March 2018. Patients with symptoms of GERD were excluded from the study. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Mazahreh et al [ 31 ] prospectively evaluated 219 patients scheduled for LSG, and 1 year later, all individuals were evaluated for the presence of symptomatic gastroesophageal reflux disease, and no significant difference was found between the two groups, so they stated that they did not require routine EGD. Gastric biopsy was performed on 148 patients.…”
Section: Is Gastroscopy Necessary Before Bariatric Surgery?mentioning
confidence: 99%
“…Mazahreh et al [ 31 ] prospectively evaluated 219 patients scheduled for LSG, and 1 year later, all individuals were evaluated for the presence of symptomatic gastroesophageal reflux disease, and no significant difference was found between the two groups, so they stated that they did not require routine EGD. Gastric biopsy was performed on 148 patients.…”
Section: Is Gastroscopy Necessary Before Bariatric Surgery?mentioning
confidence: 99%
“…(51) Retrospective studies have suggested that routine esophagogastroduodenoscopy (EGD) can be informative in preventing the cancellation or postponement of bariatric surgery in the UAE (52) and KSA, (53) whereas other studies showed no benefit in surgical management in Qatar (54) and among individuals without symptoms of gastroesophageal reflux disease in Jordan. (55) Therefore, the lack of uniform standards for preoperative care may affect compliance, implementation of evidence-based practice, and ultimately patient outcomes after bariatric surgery in the MENA region.…”
Section: Preoperative Practicesmentioning
confidence: 99%